Ibn Duraid's Linguistic Thought and Its Influence in Arabic Dictionary - Sulistya Sulistya; Jarot Wahyudi; Huseyin Emin Sert (Yayasan Adra Karima Hubbi, 2024)
Background. This study focuses on critically analyzing the method and influence of the dictionary